Dielectric Constant and Pyroelectricity for the Compounds (CH2)9(NH3)2FeCl4-xBrx(X = 0 and 1) - A. Ahmed , M.; Mousa, M.A.; El-Desoky, M.M. (Asian Journal of Chemistry, 2010)
The dielectric constant as well as the pyroelectric current for the compounds (CH2)9(NH3)2FeCl4–xBrx (x ═ 0 and 1) are measured in the temperature range including the phase transition points. The effect of replacing Cl– ions by Br–-ions on the Puckering and the canting angle of the system is discussed together with the effect of phonon-magon interaction on the dielectric constant.